Survey of veterinary antimicrobial prescribing practices, Washington State 2015. (24th December 2016) - Fowler, H.; Davis, M. A.; Perkins, A.; Trufan, S.; Joy, C.; Buswell, M.; McElwain, T. F.; Moore, D.; Worhle, R.; Rabinowitz, P. M.
Abstract : Antimicrobial resistance is a growing global health issue. It is also a recognised problem in veterinary medicine. Between September and December 2015 the authors administered a cross‐sectional survey to licensed veterinarians in Washington State to assess factors affecting antimicrobial prescribing practices among veterinarians in Washington State. Two hundred and three veterinarians completed the survey. The majority of respondents (166, 82 per cent) were engaged in small animal or exotic animal practice. 24 per cent of respondents reported not ordering culture and sensitivity (C/S) testing in practice. Of the 76 per cent of veterinarians who reported ordering C/S tests, 36 per cent reported ordering such testing 'often' or 'always' when treating presumptive bacterial infections. Most respondents (65 per cent) mentioned cost as the most common barrier to ordering a C/S test. Only 16 (10 per cent) respondents reported having access to or utilising a clinic‐specific antibiogram. This survey demonstrated that while antimicrobials are commonly used in veterinary practice, and veterinarians are concerned about antimicrobial resistance, cost is a barrier to obtaining C/S tests to guide antimicrobial therapy. Summaries of antimicrobial resistance patterns are rarely available to the practising veterinarian. Efforts to promote antimicrobial stewardship in a 'One Health' manner should address barriers to the judicious use of antimicrobials in the veterinary practice setting.